(untitled) (Research, Society and Development, 2022)
For many individuals, the dental environment refers to a situation of fear and anxiety. In order to establish a favorable environment for professionals and patients, anxiety control is of fundamental importance. This prospective, split-mouth, triple-blind, randomized clinical trial aimed to assess anxiety in patients who would undergo lower third molar extraction with minimal conscious sedation using Valerian-Hop fixed extract and Midazolam. Twelve individuals aged between 18 and 25 years, of both genders, with surgical risk classification ASA I concluded the research. To assess anxiety, the Modified Corah Dental Anxiety Scale was used in three moments. Participants received, orally, 1 capsule of Valeriana 500 mg – Hops 120 mg or Midazolam 15 mg for each side to be operated, 45 minutes before the beginning of the surgical procedure. There were no differences in anxiety scores between the 1st and 2nd surgeries for both treatments. It was possible to confirm the effectiveness of Midazolam to perform minimal conscious sedation, as the results were better than Valerian-Hop on the variable addressed, however, there is a need for further studies on the effects of the Valerian-Hop association for control of dental anxiety.